2005
DOI: 10.3998/ark.5550190.0006.614
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the reduced species of 1,4-benzoquinone with alkylated cytosine and guanine nucleobases

Abstract: The interaction of the reduced species of 1,4-benzoquinone (Q) in the presence of 1-octylcytosine and 9-ethylguanine has been studied in dimethylsulfoxide on glassy carbon electrodes. The electrochemical behavior showed that the semiquinone (Q .− ) and the quinone dianion (Q 2− ) interact with 1-octylcytosine (CH) according to a mechanism which involves only hydrogen bonding process. Contrasting with this mechanism, the nucleobase 9-ethylguanine (GH) leads to protonation of the semiquinone or the dianion, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is thus concluded that increasing acid strength with a weakly basic quinone leads to a mechanistic switch from hydrogen bonding of the semiquinone followed by its disproportionation (scheme ) to semiquinone protonation triggering an ECE−DISP process (Scheme ). Such behavior has been observed upon addition of acids on several quinones in aprotic solvents. ,, Reduction of 1,4-benzoquinone in the presence of 9-ethylguanine in DMSO follows the same mechanism, in contrast to the behavior shown with other alkylated nucleobases …”
Section: Coupling Of Electrode Electron Transfers With Proton Transfersmentioning
confidence: 78%
See 2 more Smart Citations
“…It is thus concluded that increasing acid strength with a weakly basic quinone leads to a mechanistic switch from hydrogen bonding of the semiquinone followed by its disproportionation (scheme ) to semiquinone protonation triggering an ECE−DISP process (Scheme ). Such behavior has been observed upon addition of acids on several quinones in aprotic solvents. ,, Reduction of 1,4-benzoquinone in the presence of 9-ethylguanine in DMSO follows the same mechanism, in contrast to the behavior shown with other alkylated nucleobases …”
Section: Coupling Of Electrode Electron Transfers With Proton Transfersmentioning
confidence: 78%
“…The same behavior is observed when 1,4-benzoquinone (BQ) is reduced in the presence of alkylated nucleobases in DMSO. 15,16 For example, for 1-octylthymine, the maximum number of molecules associated with the semiquinone is 2 and the association constants are 298 and 0.272 M -1 for the first and second molecules of 1-octylthymine, respectively. 15 The dianion is also hydrogen-bonded in the case of 9-octyladenine and 1-octylcytosine, but it is protonated in the case of 1-octylthymine.…”
Section: Effect Of Weak Hydrogen Bonding Agents On Quinone Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinones derivatives such as anthraquinones , and naphthoquinones (e.g., 5-hydroxy-1,4-naphthoquinone (juglone)) have been shown to interact with DNA, nucleobases being obvious H-bonding sites. The juglone was studied by considering the changes in electroactivity in the presence of nucleobases or oligonucleotides in aprotic and protic solvents . Because juglone is more sensitive to interactions with nucleobases than 1,4-benzoquinone and 1,4-naphthoquinone, it was concluded that the presence of the hydroxyl group increases H bonding with oligodeoxynucleotides (ODNs).…”
Section: Introductionmentioning
confidence: 99%
“…9 This process can be used for different applications, for example, to design building blocks for supramolecular ensembles [10][11][12][13] and also helps as an experimental system to analyze these specific interactions in compounds with biological significance. 14 Due to the high rate of both ET and PT reactions (Scheme 1), the experimental voltammograms for ETCHB processes show characteristic reversible signals which shifts towards more positive potential values for reduction processes and vice versa for oxidations. 7 However, the effect of slow ET or PT processes has not been considered systematically for the sequential pathway; in particular, slow electron transfer processes are known to be dependent on the modifications occurring in the structures of the states O and R, as referred by the Marcus and Hush model, [15][16][17] and have also been considered as a factor to discern between concerted pathways analysing the nature of the increase in the driving force of the reaction, where the reorganization energy, l t , governs the value of the intrinsic activation barrier.…”
Section: Introductionmentioning
confidence: 99%